Family Preparedness in Caring Patients with Cancer : A Literature Review - Saun, Akbar U; Rochmawati, Erna (Universitas STRADA Indonesia, 2020)
Background: Cancer patients choose to understand at home. Families have an important role in the care of clients specifically at home. Readiness is needed in order to provide optimal care and will be able to improve the quality of life of patients. This literature review aims to see how families are prepared to care for patients with cancer at home. Method: Writing this journal literature uses study literature originating from the database, namely EBSCO, PROQUEST, PubMed, and Google Scholar using the keywords Family Preparedness, Family Caregiver, Symptom Management, Palliative Care, family quality of life, Care Parenting. Using inclusion criteria that contain literature sources taken from 2009 to 2019, inclusion criteria, using English, conformity of approval keywords, linkages between the results of literature research and the discussion raised.Results: There are 4 themes found in this literature review, namely family care in patient care, instruments in measuring family readiness, self-affection for families who care for patients at home, and psycho-education in increasing family readiness to care for patients at home. Conclusion: Family readiness to treat patients at home needs to be considered. Nurses play an important role in providing education to the family in providing patient care at home so that the patient's welfare is fulfilled.